TRADISI REBU OLEH SUKU KARO YANG MERANTAU DI KOTA TANJUNG PINANG - Kristiani, Desy; Wahyuni, Sri; Solina, Emmy (Pusat Penelitian Pemberdayaan Perempuan, Gender, dan Anak UMRAH, 2022)
Abstrak The rebu tradition is a tradition of abstinence from speaking directly between in-laws adaughters-in-law as well as brothers-in-law of different sexes. The Rebu tradition is a manners that limits ways of communicating in order to maintain good relations and respect for each other, the Rebu tradition continues to be carried out by the Karo people even though they have migrated, living abroad does not make the Karo people abandon the traditions they use at home. This study aims to see how the Karo people maintain the Rebu tradition in the city of Tanjungpinang. This study uses a qualitative research with a descriptive approach. The results of the findings of this study are the Karo people maintain the Rebu tradition in Tanjungpinang city because there are good values ??in the Rebu tradition such as the value of courtesy and mutual respect not to speak carelessly and the Karo people continue to carry out Rebu in the city of Tanjungpinang. Tanjungpinang out of respect for the ancestors who have created the Rebu tradition. The Karo people maintain the overseas rebu tradition in various ways, such as carrying out the tradition wherever the community lives, keeping the tradition from losing its meaning and purpose, and passing on the tradition from generation to generation so that the Rebu tradition will continue to exist. Keywords: Karo People, Rebu Tradition, Maintaining Traditional